INDICATION, IDENTIFICATION AND INACTIVATION SALMONELLA ABORTUS-OVIS - Mussayeva А.К.; Egorova , N.N.; Yerishov , M.O.; Tlepov , A.A.; Kassenov, M.M. (Eurasian Journal of Applied Biotechnology, 2024)
The article presents the results of identification of an epizootic culture of Salmonella abortus-ovis (A) 58 isolated from parenchymatous organs of an aborted ovine fetus, inv. No. KZH 210397333, delivered from the village of Senokosnoye, Osakarovsky district, Karaganda region. To isolate a pure culture of salmonella from pathological material from the abort fetus of a ovine, the method of stepwise selection of colonies according to Drigalsky was used. The identification of the isolated culture was carried out on the basis of studying the cultural-morphological, biochemical, and antigenic properties of Salmonella abortus-ovis culture (A) 58. The culture was agglutinated with polyvalent and monoreceptor salmonella sera. According to the results of typing in AR, the culture isolated from the aborted ovine fetus was assigned to the genus Salmonella, the species abortus-ovis, serological group B. The article presents the results of experiments to optimization the process of salmonella cultivation. The passive matrix cultures of salmonella of the second generation in the exponential growth phase were used to cultivate the epizootic S. abortus-ovis (A) 58 strain. Periodic cultivation of salmonella ensured the physiologically active state of the culture, an increase in the maximum growth rate, a reduction in lag phase and a minimum generation time. The salmonella inactivation regime has been worked out, followed by seeding into liquid and dense nutrient media to determine the completeness of inactivation. It was found that effective inactivants are 10% solution of dimerethylenimine (DEI) and a 10% solution of formalin. The article presents the conditions of reactivation and cultivation of the S. abortus—ovis strain (A) 58.